Potato apical leaf curl disease Morphological and biochemical basis of resistance in potato - Reddy, P Karthik; Baswana, K S; Rana, M K; Pahuja, S K; Chug, K L; Gupta, A K (Indian Journal of Plant Protection, 2020)
Potato apical leaf curl disease (PALCD) caused by a strain of Tomato leaf curl New Delhi virus (ToLCNDV), vectored by whitefly (Bemisia tabaci) has became a threat to potato production and the identification of new domestic varieties with high levels of resistance to PALCD is required. In this study, 167 potato genotypes were evaluated for their resistance against PALCD during Rabi season of 2012-13 in Hisar, Haryana. Based on the disease reaction, out of 167 genotypes, twenty two promising varieties (13 resistant, 4 moderately resistant and 5 susceptible) were selected for detailed study during Rabi season of 2013-14. Trichomes, phenols and ortho-dihydroxy phenols were maximum in the disease free genotype Kufri Bahar and low in all the susceptible genotypes. The number of stomata, leaf area, and total sugars and whitefly population was found correlated with per cent PALCD incidence, while it had significantly negative correlation with number of trichomes, phenol content and ortho-dihydroxy phenols. Whitefly population was high in susceptible genotypes like Kufri Khyati and Kufri Pukhraj. Kufri Bahar and AICRP-PH-2 were completely free from PALCD whereas, Kufri Khyati was highly susceptible.